What is a relation between data analytics and medical diagnostics? - Babič, František; Paralič, Ján; Vadovský, Michal; Muchová, Miroslava; Lukáčová, Alexandra; Vantová, Zuzana (International journal on biomedicine and healthcare, 2017)
Data Analytics provides various methods and approaches to extract hidden and poten-tially useful knowledge for different purposes. It means that we can use this knowledge for decision support, e.g. to identify crucial inputs and relations, to predict some future state, to confirm or reject our hypothesis. The medical diagnostics deals with all the mentioned tasks to provide a right diagnosis for the patient and to ensure the effective diagnostic process. In this paper, we briefly describe some of our activi-ties oriented to support medical diagnostics by means of Data Analytics approaches; we selected only key points here, more details can be found in our previously pub-lished articles.
Keywords: algoritmy; Decision Support Techniques; Statistics as Topic; Data Interpretation, Statistical; metody pro podporu rozhodování; Clinical Decision-Making; statistika jako téma; interpretace statistických dat; klinické rozhodování; Algorithms